2009
DOI: 10.1097/nnr.0b013e3181902b93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nurse-Managed Program on Hepatitis A and B Vaccine Completion Among Homeless Adults

Abstract: Background-Hepatitis B virus (HBV) infection constitutes a major health problem for homeless persons. Ability to complete an HBV vaccination series is complicated by the need to prioritize competing needs, such as addiction issues, safe places to sleep, and food, over health concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 28 publications
2
75
0
Order By: Relevance
“…However, all of the 28 citations focusing on the particularities of Traveller Communities were used in developing the 'to whom' initial theory (see Chapter 3, 'To whom': the context of outreach work), the 40 citations contributing some theoretical understandings contributed to the development of the explanatory framework for outreach detailed in Chapter 3 (see Explanatory framework). The 18 studies featuring stronger research designs (from RCTs to phenomenological studies) included outreach type interventions in aboriginal communities in Australia and Canada, 101 homeless people, 102 native American, 103,104 and refugee groups 105 as well as disaffected drug users. 106 These studies were used to substantiate the developing theories, for example on p. 57 and p. 64.…”
Section: Thematic Analysis Of the Data Extractedmentioning
confidence: 99%
“…However, all of the 28 citations focusing on the particularities of Traveller Communities were used in developing the 'to whom' initial theory (see Chapter 3, 'To whom': the context of outreach work), the 40 citations contributing some theoretical understandings contributed to the development of the explanatory framework for outreach detailed in Chapter 3 (see Explanatory framework). The 18 studies featuring stronger research designs (from RCTs to phenomenological studies) included outreach type interventions in aboriginal communities in Australia and Canada, 101 homeless people, 102 native American, 103,104 and refugee groups 105 as well as disaffected drug users. 106 These studies were used to substantiate the developing theories, for example on p. 57 and p. 64.…”
Section: Thematic Analysis Of the Data Extractedmentioning
confidence: 99%
“…Prior studies have shown that HCV patient education may play an important role in increasing willingness to accept HCV treatment (Gupta, Romney, Briggs, & Benker, 2007; Surjadi et al 2011). Similarly, educational programs targeting other high risk populations for HBV have shown that education is a key component in increasing willingness to be screened for and vaccinated against HAV and HBV (Nyamathi et al 2009). Drug treatment programs offer an important opportunity to engage and encourage dialogue concerning viral hepatitis prevention and treatment among its patients, and to support drug users’ hepatitis-related health care needs (Strauss et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nurse led interventions (Day et al, 2011;Nyamathi et al, 2009) integrated with youth development and leadership programmes that promote pro-social bonding, cognitive, social and emotional competence and self-determination (Gavin, Catalano, David-Ferdon, Gloppen, & Markham, 2010) may offer a way forward for homeless youth health service programming. In terms of nursing practice this may involve collaborative community based work that brings together professionals across the education, youth and family support, justice and health sectors.…”
Section: Implications For Nursing Practice and Future Researchmentioning
confidence: 99%